Pengaruh Biaya Lingkungan Dan Pengungkapan Lingkungan Terhadap Nilai Perusahaan Dengan Dewan Komisaris Independen Sebagai Pemoderasi - Regina Theresia Eku; Hasnawati Hasnawati (Pusat Riset dan Inovasi Nasional, 2024)
This research was conducted because researchers wanted to know the influence of environmental costs, environmental disclosure and environmental performance on company value with an independent board of commissioners as moderator in manufacturing companies in Indonesia during the period 2021 to 2022. This research is a replication of Hidayat et al's research. al., (2023)